Klaus Jarmatz et al., eds.: Kritik in der Zeit. Literaturkritik der DDR - Michael L Burwell (GDR Bulletin, 1979)
2nd edition. Halle/Leipzig: Mitteldeutscher Verlag, 1978. 2 vols., 453 and 485 p. 21,-.